2020
DOI: 10.3389/fmed.2020.00547
|View full text |Cite
|
Sign up to set email alerts
|

Viral Transmission and Clinical Features in Asymptomatic Carriers of SARS-CoV-2 in Wuhan, China

Abstract: We report the clinical characteristics, viral shedding duration, and contact tracing for asymptomatic carriers of SARS-CoV-2 in Wuhan, China. The asymptomatic carriers were relatively young (median age: 34.5 years). Chest computed tomography showed no abnormalities. The nasopharyngeal swab was an optimum specimen for RNA testing. The median viral shedding duration was 11.5 days. Notably, 2 months of viral shedding duration were reported in two nurses, which was much longer than previously reported or than usua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
(29 reference statements)
0
9
0
Order By: Relevance
“…While asymptomatic testing following exposure has increased in recent months, the current testing strategy in the U.S. still predominantly targets symptomatic patients despite estimates that asymptomatic patients represent 40–45% of infected individuals 10 , 72 . Transmission during the incubation period has been reported, and the viral load of symptomatic and asymptomatic patients is similar 73 76 . The relationship between SARS-CoV-2 viral shedding and risk of transmission is unclear, and the percentage of transmission attributable to asymptomatic or pre-symptomatic infection of SARS-CoV-2 is unknown 77 .…”
Section: Discussionmentioning
confidence: 95%
“…While asymptomatic testing following exposure has increased in recent months, the current testing strategy in the U.S. still predominantly targets symptomatic patients despite estimates that asymptomatic patients represent 40–45% of infected individuals 10 , 72 . Transmission during the incubation period has been reported, and the viral load of symptomatic and asymptomatic patients is similar 73 76 . The relationship between SARS-CoV-2 viral shedding and risk of transmission is unclear, and the percentage of transmission attributable to asymptomatic or pre-symptomatic infection of SARS-CoV-2 is unknown 77 .…”
Section: Discussionmentioning
confidence: 95%
“…This result was also verified in Zhejiang, China, where, among 36 children with confirmed COVID-19, 28% were asymptomatic carriers ( 13 ). Tan et al ( 14 ) identified that asymptomatic carriers were relatively young (mean age, 34.5 years old). Current evidence suggests that the asymptomatic carriers with SARS-CoV-2 vary by age, however, to the best of our knowledge, no studies have identified differences in sex between asymptomatic carriers.…”
Section: Demographic Characteristicsmentioning
confidence: 99%
“…The study by Liu et al ( 9 ) showed that the secondary attack rate of 131 asymptomatic carriers was 2.6% (24/914), while the secondary attack rate of 16 confirmed cases was 9.7% (23/236), further demonstrating that the transmission risk of asymptomatic carriers was decreased compared with that of the confirmed cases. In China, a study including 12 asymptomatic carriers in Wuhan also identified that only one carrier has transmitted the virus to a close contact ( 14 ). Chen et al ( 39 ) tracked 9 asymptomatic carriers and identified that none of them had transmitted SARS-CoV-2 to others, so they speculated that the absence of symptoms such as sneezing and coughing may interfere with virus shedding and decrease the risk of infection.…”
Section: Infectivity and Transmission Risk Of Asymptomatic Carriermentioning
confidence: 99%
See 1 more Smart Citation
“…The proportion of Ig G + in patients with asymptomatic infection at the screening point was 72% (95% CI: 46–92%, I 2 = 94.2%, k = 8, n = 268; Figure 4 ) ( 17 , 25 , 26 , 40 , 51 , 56 , 58 , 60 ).…”
Section: Resultsmentioning
confidence: 99%